Characteristics of the Precipitation Diurnal Variation and Underlying Mechanisms Over Jiangsu, Eastern China, During Warm Season - Mu, Xiyu; Huang, Anning; Wu, Yang; Xu, Qi; Zheng, Yuanyuan; Lin, Huijuan; Fang, Dexian; Zhang, Xindan; Tang, Yong; Cai, Shuxin (Frontiers in Earth Science, 2021)
Based on the hourly precipitation observed from ~1800 automatic rain gauges during 2013-2017, characteristics of precipitation diurnal variation and underlying mechanisms over Jiangsu Province, Eastern China during the warm season (May to September) have been revealed in this study. Results show that the precipitation amount (PA), frequency (PF) and intensity (PI) are zonally distributed over Jiangsu. The precipitation shows distinct diurnal cycle and zonal distribution. The large precipitation is located over the southwest side of the Jiangsu Section of Yangtze River (JSYR). From midnight to noon, the precipitation expands northeastward, but the precipitation shrinks southeastward from noon to midnight. Meanwhile, the PA is larger during daytime than that during nighttime over most Jiangsu. In addition, the PA shows two diurnal peaks with one in the early morning mainly contributed by the long duration rainfall and the other in the afternoon resulted from the short duration rainfall. The total rainfall is largely contributed by the long duration rainfall. During the whole warm season, water vapor convergence (divergence) and ascending (sinking) movements are consistent, corresponding to the long duration precipitation diurnal cycles.The contribution of rainfall with long (short) duration to the total rainfall over most areas shows very distinct sub-seasonal variations with a clear decreasing (increasing) trend from pre-Meiyu through Meiyu to post Meiyu. Among the three sub-periods in warm season, the PA and diurnal cycle of the total rainfall are mostly contributed by those during the Meiyu period. The long duration precipitation is closely related to the enhancement of the water vapor convergence during the pre-Meiyu period. However, during the Meiyu and post-Meiyu periods the long duration precipitation is more consistent with the dynamic lift since the water vapor is abundant. Concluded from the cluster analysis, precipitation spatial distributions are closely associated with the underlying surface, such as the Yangtze River, big cities, Lake Taihu, Lake Hongze and complex coastal lines. The diurnal variation of the rainfall over different underlying surface shows respective diurnal cycle features.